"Books Are Not Absolutely Dead Things": Milton Speaks to Freedom of Information in Botswana from the Grave through Areopagitica. (2nd September 2017) - Koketso, Daniel; Kgafela-Mokoka, K. N.
ABSTRACT: On July 8, 2010, the Botswana National Assembly resolved, in accordance with the provisions of the Standing Order 60(2), to allow the then Member of Parliament for Gaborone Central, Hon. Dumelang Saleshando, to bring before Parliament a Private Member's Bill that would allow for the enactment of a Freedom of Information Act. The bill was intended to extend the right of members of the public to access information in the possession of public authorities. This paper critically examines the fundamental provisions of the bill in the light of Miltonic ideas about the liberty of unlicensed printing expressed in Areopagitica . The paper argues using the functional theory that the bill speaks to the ideals of Milton's advocacy in 1644 of freedom of publication, such as the search for truth, the acquisition of knowledge of good and evil in the fallen world as well as the exercise of temperance.